Ata Mbeko Tepo: Pilihan Pengobatan Tradisonal Patah Tulang pada Masyarakat Desa Ruang - Nuheng, Maria Restiana; Sudiarna, I Gusti Putu; Laksmiwati, Ida Ayu Alit (Sunari Penjor : Journal of Anthropology, 2023)
The development of the modern medical system is sometimes less able to efficiently answer various health problems experienced by the community. In handling fractures, the people of Ruang Village in come to ata mbeko tepo. This can be seen in the beliefs and habits of the people of Ruang Village who use the services of ata mbeko tepo. This study aims to explain the fracture treatment technique through ata mbeko tepo and explain the survival factors of ata mbeko tepo. Using the service of ata mbeko tepo in the treatment of fractures by the people of Ruang Village will use the theory of health behavior and theory of symbolic interaction, meanwhile the reason for the people of Ruang Village still choose ata mbeko tepo for the treatment of fractures using the theory of health belief model. This research uses qualitative research methods with ethnographic research models through observation techniques and interview. The result of the research show that the fracture treatment technique  through ata mbeko tepo, improved massage techniques, massaged, and pulled the broken bone to return it to its original position.